Faculty Senate, Minutes, March 20, 2008 - Faculty Senate, Valdosta State University (Valdosta, Ga: Valdosta State University Archives and Special Collections, 2008)
Valdosta State University. Faculty Senate, Minutes, March 20, 2008. Chairperson, Ronald M. Zaccari; Vice Chairperson, Louis Levy; Executive Secretary, Christine James; Parliamentarian, Richard Haptonstall;
1 electronic document. Faculty Senate, Minutes, March 20, 2008. 31 pages.
Keywords: Valdosta State University. Faculty Senate; Minutes (Records); Committees; Electronic records